'Cracking a Strange Veiled Code': Language Learning Experiences of North Americans in South Asia. (6th June 2017) - Perera, Kaushalya
Abstract: Memoirs and autobiographical writing on language learning provide perspectives on migration and residence in North America and Europe for the most part, where struggle and loss are some of the recurrent themes (Aneta Pavlenko 2001a ; Besemeres 2004 ; Kinginger 2004a ). An unaddressed aspect of foreign language learning remains the 'reverse' experience of individuals from these regions learning languages of other regions. The aim is to provide an account of such experiences, based on language memoirs by North American women writing of their foreign language learning experiences in South Asia. In addition to typical issues of pedagogical interest such as the long-term process of language learning and the role of affect, this article discusses the language ideologies of Western learners in South Asia as well as literacy development in new orthographies. These language memoirs provide us with highly contextualized accounts of foreign language learning from infrequently studied contexts.